Method for preparing high-temperature-resistant furnace lining material of intermediate frequency furnace

By adopting non-uniform gradient distribution of quartz sand and staged sintering processes in the medium-frequency furnace lining materials, the problems of low density and poor thermal shock resistance of existing materials are solved, and the high-temperature densification and thermal shock resistance of the materials are achieved.

CN119591393APending Publication Date: 2025-03-11CHIFENG CITY JIANZHI PIPE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411820301.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing medium-frequency furnace lining materials have poor particle size distribution design and insufficient sintering process, low density and poor thermal shock resistance.

Method used

The non-uniform gradient distribution design of high-purity quartz sand is adopted, with the ratio of the maximum particle size to the minimum particle size greater than 60, and the fine-grained quartz sand accounts for 20% to 30% of the total weight; through layer-by-layer thin layer tamping and phased gradual heating sintering process, the high-temperature densification and thermal shock resistance of the material are achieved.

Benefits of technology

It significantly improves the compactness and thermal shock resistance of the material, extends the service life of the furnace lining, and is suitable for long-term and efficient operation of medium-frequency furnaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591393A_ABST
    Figure CN119591393A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a high-temperature-resistant furnace lining material of an intermediate frequency furnace. The method comprises the following steps: proportioning raw materials: weighing high-purity quartz sand and boric acid according to a weight ratio; wherein the quartz sand comprises a plurality of particle size ranges covering at least five particle sizes, the quartz sand of each particle size in the quartz sand composition adopts a non-uniform gradient distribution mode, the minimum particle size is fine-particle-size quartz sand with the particle size range of 120-150 meshes, and the quartz sand accounts for 20-30% of the total weight of the quartz sand; the dosage of the boric acid is 0.8-1.5% of the total weight of the quartz sand; mixing: fully mixing the quartz sand and boric acid through mixing equipment to form a uniform mixture; forming: paving the mixture in the furnace wall in a layer-by-layer thin-layer tamping manner; and baking: gradually heating the furnace lining material in stages, and finishing high-temperature baking and sintering in stages. According to the method, tight combination among particles can be promoted through staged sintering, a compact overall structure is formed, and meanwhile the service life of the furnace lining can be effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of refractory material preparation, and in particular to a method for preparing a high-temperature resistant lining material for a medium-frequency furnace. Background Art

[0002] The medium frequency furnace is a smelting equipment widely used in the metallurgical and foundry industries. Its high efficiency and energy saving make it occupy an important position in industrial production. However, as an important part of the medium frequency furnace, the lining material needs to withstand high temperature, high thermal shock, and chemical erosion of molten metal and slag. The performance of the lining material directly affects the service life, operating cost and production efficiency of the medium frequency furnace. Therefore, how to improve the high temperature resistance, thermal shock resistance and density of the lining material has always been a key research direction in related fields.

[0003] At present, the common medium frequency furnace lining material is made of quartz sand as the main component, which is prepared by mixing sand materials of different particle sizes and adding an appropriate amount of binder. The usual production process includes four steps: screening, mixing, molding and sintering of raw materials. In actual production, the distribution of quartz sand particle size directly affects the density and thermal shock resistance of the furnace lining material, while the sintering process determines the adequacy of the quartz sand crystal transformation and the high-temperature stability of the material. However, the existing technology still has shortcomings in these key links. For example, the role of sand materials of different particle sizes is not sufficiently considered in the particle size distribution design, making it difficult to achieve effective filling and overall density between particles. In addition, the temperature control and segmented design of the sintering process are simple, resulting in incomplete crystal transformation of quartz sand, making it difficult for the material's thermal shock resistance to meet the needs of high-temperature smelting. Summary of the invention

[0004] The present application provides a method for preparing a high temperature resistant lining material for a medium frequency furnace, so as to solve the problem that the existing lining material has low density and affects the thermal shock resistance due to unreasonable particle size distribution design and insufficient sintering process.

[0005] The present application provides a method for preparing a high temperature resistant lining material for a medium frequency furnace, comprising the following steps:

[0006] Raw material ratio: high-purity quartz sand and boric acid are weighed according to weight ratio; wherein the quartz sand includes a plurality of particle size ranges covering at least five particle sizes, and the quartz sand of each particle size in the quartz sand composition adopts a non-uniform gradient distribution mode, the ratio of the maximum particle size to the minimum particle size of the quartz sand is greater than 60, the minimum particle size is fine-grained quartz sand with a particle size range of 120 to 150 meshes, and the fine-grained quartz sand with a particle size range of 120 to 150 meshes accounts for 20% to 30% of the total weight of the quartz sand; the amount of boric acid used is 0.8% to 1.5% of the total weight of the quartz sand;

[0007] Mixing: The quartz sand and boric acid are fully mixed by a mixing device to form a uniform mixture; a small amount of water is added to the mixture during the mixing process, and the weight proportion of the water does not exceed 0.8% of the total weight of the mixture;

[0008] Forming: The mixed material is laid on the furnace wall in a thin layer-by-layer tamping manner, with each layer thickness not exceeding 5 mm; mechanical vibration equipment is used to assist in the tamping process to improve density and adhesion;

[0009] Baking: The furnace lining material is heated up gradually in stages, and the sintering temperature is 1250-1400℃. High-temperature baking and sintering are completed in stages to achieve the crystal transformation of quartz sand and structural densification of the material.

[0010] In an optional embodiment, the particle size range of the quartz sand used includes the following particle sizes: 2-4 mesh, 4-6 mesh, 6-8 mesh, 8-10 mesh, 10-20 mesh, 20-40 mesh, 40-70 mesh and 120-150;

[0011] When mixing the raw materials, weigh the raw materials according to the following weight percentages:

[0012] High-purity quartz sand with a particle size of 2 to 4 mesh: 4% to 6%;

[0013] High-purity quartz sand with a particle size of 4-6 mesh: 5%-7%;

[0014] High-purity quartz sand with a particle size of 6-8 mesh: 5%-7%;

[0015] High-purity quartz sand with a particle size of 8-10 mesh: 10%-14%;

[0016] High-purity quartz sand with a particle size of 10-20 mesh: 16%-18%;

[0017] High-purity quartz sand with a particle size of 20-40 mesh: 16%-18%;

[0018] High-purity quartz sand with a particle size of 40-70 mesh: 12%-14%;

[0019] High-purity quartz sand with a particle size of 120-150 mesh: 22%-24%;

[0020] The dosage of boric acid is 1.0% to 1.3% of the total weight of quartz sand.

[0021] In an optional embodiment, when mixing the raw materials, the raw materials are weighed according to the following weight percentages:

[0022] High-purity quartz sand with a particle size of 2 to 4 mesh: 5%;

[0023] High-purity quartz sand with a particle size of 4-6 mesh: 6%;

[0024] High-purity quartz sand with a particle size of 6-8 mesh: 6%;

[0025] High-purity quartz sand with a particle size of 8-10 mesh: 12%;

[0026] High-purity quartz sand with a particle size of 10-20 mesh: 17.5%;

[0027] High-purity quartz sand with a particle size of 20-40 mesh: 17.5%;

[0028] High-purity quartz sand with a particle size of 40-70 mesh: 12.5%;

[0029] High-purity quartz sand with a particle size of 120-150 mesh: 23.5%;

[0030] The amount of boric acid used is 1.2% of the total weight of quartz sand.

[0031] In an optional embodiment, a planetary mixing device is used for mixing, and the speed of the device is controlled to be 50 to 120 rpm during the mixing process. The added water is uniformly introduced by spraying and is gradually added during the mixing process. The addition time is controlled within 3 to 5 minutes, and the mixing time is 5 to 10 minutes, until a mixture with good uniformity is formed.

[0032] In an optional embodiment, during the baking stage, the furnace lining material is subjected to a sintering process of gradually increasing the temperature in stages as follows:

[0033] Initial heating stage: gradually raise the temperature from room temperature to 200°C to remove moisture and volatile impurities in the mixture;

[0034] Intermediate heating stage: gradually increase the temperature from 200°C to 1250°C and keep it at 600-800°C for 2-4 hours to achieve the initial transformation of the low-temperature crystal form of quartz sand to the high-temperature crystal form and reduce the pores between the particles;

[0035] Final heating stage: gradually increase the temperature from 1250°C to 1350-1400°C and keep it warm for 4-6 hours to achieve a full transformation of the quartz sand crystal form and form a dense high-temperature bonding structure between the particles;

[0036] The heating rate of the entire sintering process is controlled at 0.5-1°C / minute and lasts for no less than 36 hours.

[0037] In an optional embodiment, the forming step comprises:

[0038] The mixture is laid layer by layer on the furnace wall by combining mechanical vibration equipment and manual tamping tools; the thickness of each layer is 3 to 5 mm;

[0039] Use mechanical vibration equipment to vibrate and compact each layer of the mixture at a frequency of 300 to 500 times per minute and a vibration time of 30 to 60 seconds;

[0040] After each layer is laid, manual tamping tools are used to perform additional compaction on the corners and complex areas to ensure overall density and uniformity.

[0041] In an optional embodiment, the mechanical vibration device used is a handheld high-frequency vibrator, and the manual tamping tool used is a metal impact hammer, the hammer head of the metal impact hammer is a conical metal structure, and the weight of the hammer head is 0.5 to 1.5 kilograms.

[0042] In an optional embodiment, during the sintering process, an infrared temperature control device is used to monitor the temperature in real time during the insulation stage of 600-800°C, and the temperature difference is controlled within ±2°C.

[0043] In an optional embodiment, the temperature of the water added during the mixing process is 20°C to 40°C.

[0044] In an optional embodiment, the silicon dioxide content of the high-purity quartz sand used is not less than 99.9%.

[0045] Compared with the prior art, this application has the following beneficial effects:

[0046] 1. When preparing the high-temperature resistant lining material of the medium-frequency furnace in the present application, the quartz sand in the raw material is used to cover at least five particle sizes, and a non-uniform gradient distribution method is adopted. The ratio of the maximum particle size to the minimum particle size is greater than 60, and the fine-grained quartz sand (particle size of 120-150 mesh) accounts for 20% to 30% of the total weight of the quartz sand. This particle size distribution design realizes the optimized stacking of particles inside the material. The fine-grained quartz sand can fill the gaps between the particles at a higher ratio, effectively reducing the porosity of the material, thereby improving the density of the material, which is helpful to achieve densification of the furnace lining material in subsequent sintering.

[0047] 2. In terms of the molding process, the thin layer tamping method allows the mixture to be evenly laid in the furnace wall, and the thickness of each layer is controlled to be no more than 5 mm. At the same time, the auxiliary tamping with mechanical vibration equipment not only helps to enhance the density of the mixture, but also improves the adhesion between the material and the furnace wall. The present application adopts such a method, which can effectively avoid the delamination and cracking problems caused by excessive thickness in traditional thick layer molding, while ensuring the uniformity of the entire furnace lining material. This process is particularly suitable for the complex shape of the furnace wall structure of the medium frequency furnace, and can provide more stable support under high temperature conditions and extend the service life of the furnace lining.

[0048] 3. During the sintering process, a staged and gradual temperature increase design is adopted, and the sintering temperature is controlled at 1250-1400°C. This process can effectively avoid the problem of thermal stress concentration caused by a sudden temperature rise, so that the quartz sand particles can gradually complete the crystal transformation of quartz sand during the baking and sintering process, so that the quartz sand can achieve a more sufficient crystal transformation, thereby significantly improving the high-temperature stability of the material. In addition, the present application can promote the close bonding between particles through staged sintering to form a dense overall structure, so that the furnace lining material exhibits excellent thermal shock resistance in a high-temperature smelting environment, and at the same time effectively extends the service life of the furnace lining, providing a solid guarantee for the long-term and efficient operation of the medium-frequency furnace. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0050] Figure 1 A flow chart of a method for preparing a high temperature resistant lining material for a medium frequency furnace provided in one embodiment of the present application. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.

[0052] The present application provides a method for preparing a high temperature resistant lining material for a medium frequency furnace, including four processes: raw material proportioning, mixing, molding and baking. Figure 1 As shown, the method for preparing the high temperature resistant lining material of the medium frequency furnace comprises the following steps:

[0053] Step S101, weighing high-purity quartz sand and boric acid according to weight ratio;

[0054] The quartz sand includes a plurality of particle size ranges covering at least five particle sizes, the quartz sand of each particle size in the quartz sand composition adopts a non-uniform gradient distribution mode, the ratio of the maximum particle size to the minimum particle size of the quartz sand is greater than 60, the minimum particle size is the fine-grained quartz sand with a particle size range of 120 to 150 meshes, and the fine-grained quartz sand with a particle size range of 120 to 150 meshes accounts for 20% to 30% of the total weight of the quartz sand; the amount of boric acid used is 0.8% to 1.5% of the total weight of the quartz sand;

[0055] Step S102, fully mixing quartz sand and boric acid through a mixing device to form a uniform mixture;

[0056] A small amount of water is added to the mixture during the mixing process, and the weight proportion of water does not exceed 0.8% of the total weight of the mixture;

[0057] Step S103, laying the mixed material on the furnace wall in a thin layer-by-layer tamping manner, with each layer thickness not exceeding 5 mm;

[0058] Mechanical vibration equipment is used to assist in the tamping process to improve density and adhesion;

[0059] Step S104, gradually heating the furnace lining material in stages, with the sintering temperature being 1250-1400°C, and completing high-temperature baking and sintering in stages to achieve the crystal transformation of the quartz sand and the densification of the material structure.

[0060] In the embodiment of the present application, when preparing the high-temperature resistant lining material of the medium-frequency furnace, the quartz sand in the raw material is used to cover at least five particle sizes, and a non-uniform gradient distribution method is adopted. The ratio of the maximum particle size to the minimum particle size is greater than 60, and the fine-grained quartz sand (particle size of 120-150 mesh) accounts for 20% to 30% of the total weight of the quartz sand. This particle size distribution design realizes the optimized stacking of particles inside the material. The fine-grained quartz sand can fill the gaps between the particles at a higher proportion, effectively reducing the porosity of the material, thereby improving the density of the material, which helps to densify the lining material in subsequent sintering.

[0061] Optionally, the quartz sand is pretreated before being weighed, and the process is as follows: the quartz sand is screened using a standard sieve to ensure that the particle size range of each particle size is strictly controlled within the specified range (such as 2-4 mesh, 4-6 mesh, etc.). After screening, the quartz sand of different particle sizes is graded and stored to avoid cross contamination. The quartz sand is then cleaned to remove the silt and organic impurities on the surface. The cleaned quartz sand is dried to prevent residual moisture from affecting the mixing uniformity.

[0062] Optionally, the boric acid may be pretreated using any pretreatment method.

[0063] Screening treatment: Use a 100-mesh fine screen to screen the boric acid to make its particle size uniform and prevent larger particles from entering the mixture.

[0064] Moisture-proof storage: Boric acid should be sealed during storage to avoid moisture and agglomeration. If the boric acid has slightly agglomerated, it can be restored to fluidity by slight crushing (such as manual grinding).

[0065] In terms of the molding process, the embodiment of the present application adopts a layer-by-layer thin-layer tamping method, so that the mixture can be evenly laid in the furnace wall, and the thickness of each layer is controlled to be no more than 5 mm. At the same time, the auxiliary tamping with mechanical vibration equipment not only helps to enhance the density of the mixture, but also improves the adhesion between the material and the furnace wall. The present application adopts such a method, which can effectively avoid the delamination and cracking problems caused by excessive thickness in traditional thick layer molding, while ensuring the uniformity of the entire furnace lining material. This process is particularly suitable for the complex shape of the furnace wall structure of the medium frequency furnace, and can provide more stable support under high temperature conditions and extend the service life of the furnace lining.

[0066] During the sintering process, the embodiment of the present application adopts a staged and gradual temperature increase design, and the sintering temperature is controlled at 1250-1400°C. This process can effectively avoid the problem of thermal stress concentration caused by the sudden temperature rise, so that the quartz sand particles can gradually complete the crystal transformation of quartz sand during the baking and sintering process, so that the quartz sand can achieve a more sufficient crystal transformation, thereby significantly improving the high-temperature stability of the material. In addition, the present application can promote the close bonding between particles through staged sintering to form a dense overall structure, so that the furnace lining material exhibits excellent thermal shock resistance in a high-temperature smelting environment, and at the same time effectively extends the service life of the furnace lining, providing a solid guarantee for the long-term and efficient operation of the medium-frequency furnace.

[0067] In some embodiments, the particle size range of the quartz sand used includes the following particle sizes: 2-4 mesh, 4-6 mesh, 6-8 mesh, 8-10 mesh, 10-20 mesh, 20-40 mesh, 40-70 mesh and 120-150 mesh;

[0068] When mixing the raw materials, weigh the raw materials according to the following weight percentages:

[0069] High-purity quartz sand with a particle size of 2 to 4 mesh: 4% to 6%;

[0070] High-purity quartz sand with a particle size of 4-6 mesh: 5%-7%;

[0071] High-purity quartz sand with a particle size of 6-8 mesh: 5%-7%;

[0072] High-purity quartz sand with a particle size of 8-10 mesh: 10%-14%;

[0073] High-purity quartz sand with a particle size of 10-20 mesh: 16%-18%;

[0074] High-purity quartz sand with a particle size of 20-40 mesh: 16%-18%;

[0075] High-purity quartz sand with a particle size of 40-70 mesh: 12%-14%;

[0076] High-purity quartz sand with a particle size of 120-150 mesh: 22%-24%;

[0077] The sum of the weight percentages of the above 8 groups of quartz sand is 100%, and the amount of boric acid used is 1.0% to 1.3% of the total weight of the quartz sand.

[0078] The larger the mesh number of the above 8 groups of quartz sand, the finer the quartz sand particles. Taking the high-purity quartz sand with a particle size range of 120-150 mesh as an example, the particle size range is 120-150 mesh. The quartz sand particles whose surface can pass through the 120 mesh sieve but are retained by the 150 mesh sieve have a particle size range between the apertures corresponding to the 20 mesh sieve and the 40 mesh sieve.

[0079] In the embodiment of the present application, fine-grained quartz sand with a minimum particle size of 120-150 mesh is selected, and quartz sand with a higher mesh number (such as 200 mesh or above) is not further used, mainly based on the comprehensive considerations of the following aspects:

[0080] First, from the perspective of the effect of particle size on material properties, sand particles with higher mesh counts (i.e., finer particle size) have larger surface areas and better filling properties, which can further reduce the porosity of the material. However, excessive use of ultra-fine particle size sand will bring the following problems:

[0081] Finer particles have smaller particle spacing during sintering, and the sintering shrinkage rate increases significantly, which may cause material cracking or dimensional instability. In addition, finer sand may excessively reduce the permeability of the material, affecting the heat dissipation and stress release performance of the furnace lining material during high-temperature operation. Fine-grained sand of 120-150 mesh has a moderate particle size, which can fill larger particle gaps without excessively reducing the permeability of the material and balancing the sintering shrinkage rate. Using fine-grained sand in this particle size range can achieve a balance between material density and high-temperature stability.

[0082] In addition, from the perspective of process operation, quartz sand powder with a higher mesh number is very easy to absorb moisture and agglomerate, and is easy to adhere to the surface of the equipment during the mixing process, resulting in poor mixing uniformity, thus affecting the overall performance of the furnace lining material. Moreover, when the sand material is too fine, the problem of insufficient bonding between layers may occur during the layer-by-layer tamping and forming, especially in complex parts (such as corners), which is easy to form weak areas with uneven density.

[0083] 120-150 mesh quartz sand is a common and mature particle size in industrial production. The material supply cost is relatively low, and it has good controllability when combined with other particle size sands. Using sand with higher mesh will increase production costs and also place higher requirements on mixing and molding equipment.

[0084] In this embodiment, the particle size distribution design of quartz sand covers a variety of particle size ranges from 2 to 4 meshes to 120 to 150 meshes, and adopts a non-uniform gradient distribution method, which enables the coarse-grained quartz sand to form a solid skeleton structure in the material, while the quartz sand in the medium-sized particle size range can fill the larger gaps between the skeletons, thereby providing a stable particle support system. At the same time, fine-grained quartz sand (120 to 150 meshes, accounting for 22% to 24%) can further fill tiny gaps and effectively reduce the porosity inside the material. Through this multi-level particle size distribution optimization, the bulk density of the material can be significantly improved, thereby laying a good foundation for the subsequent molding and sintering process.

[0085] The present embodiment sets a specific weight percentage range for quartz sand of each particle size range, i.e., high-purity quartz sand with a particle size of 2 to 4 mesh: 4% to 6%; high-purity quartz sand with a particle size of 4 to 6 mesh: 5% to 7%; high-purity quartz sand with a particle size of 6 to 8 mesh: 5% to 7%; high-purity quartz sand with a particle size of 8 to 10 mesh: 10% to 14%; high-purity quartz sand with a particle size of 10 to 20 mesh: 16% to 18%; high-purity quartz sand with a particle size of 20 to 40 mesh: 16% to 18%; high-purity quartz sand with a particle size of 40 to 70 mesh: 12% to 14%; high-purity quartz sand with a particle size of 120 to 150 mesh: 22% to 24%. This ratio range design provides flexible adjustment space for actual production. Different furnace lining application scenarios have different requirements for the compressive strength, heat resistance or thermal shock resistance of the material. By adjusting the particle size ratio, targeted optimization can be achieved. For example, under high temperature and drastic fluctuation conditions, appropriately increasing the proportion of fine-grained quartz sand can further improve the density and thermal stability of the material. This flexibility enables the material performance to better adapt to a variety of usage environments.

[0086] At the same time, this embodiment clarifies that the dosage range of boric acid is 1.0% to 1.3% of the total weight of quartz sand. This ratio not only avoids the enhanced corrosiveness caused by excessive boric acid, but also gives full play to the role of boric acid as a high-temperature binder. During the high-temperature sintering process, boric acid can promote the chemical bonding between quartz sand particles and improve the compressive strength and high temperature resistance of the material. In addition, reasonable control of the amount of boric acid added can also reduce the generation of volatile substances during the sintering process and further improve the thermal stability of the material. This method provides a reliable guarantee for the long-term stable use of material performance.

[0087] In some embodiments, when mixing the raw materials, the raw materials are weighed according to the following weight percentages:

[0088] High-purity quartz sand with a particle size of 2 to 4 mesh: 5%;

[0089] High-purity quartz sand with a particle size of 4-6 mesh: 6%;

[0090] High-purity quartz sand with a particle size of 6-8 mesh: 6%;

[0091] High-purity quartz sand with a particle size of 8-10 mesh: 12%;

[0092] High-purity quartz sand with a particle size of 10-20 mesh: 17.5%;

[0093] High-purity quartz sand with a particle size of 20-40 mesh: 17.5%;

[0094] High-purity quartz sand with a particle size of 40-70 mesh: 12.5%;

[0095] High-purity quartz sand with a particle size of 120-150 mesh: 23.5%;

[0096] The amount of boric acid used is 1.2% of the total weight of quartz sand.

[0097] This embodiment provides the weight percentage of each raw material when mixing raw materials, and refines the raw material mixing scheme. This fixed ratio design reduces the variables in actual operation and ensures the consistency of raw materials in each batch of production. Especially in industrial large-scale production, the accuracy of raw material ratio helps to reduce the performance difference between batches and ensure the stable performance of finished furnace lining materials. At the same time, this precise ratio provides a predictable basis for subsequent mixing, molding and sintering links, optimizing the overall production process.

[0098] In this embodiment, the proportion of fine-grained quartz sand (particle size range 120-150 mesh) is 23.5%, and the fine-grained sand has a significant effect on filling tiny pores and improving the density of the material. During high-temperature sintering and actual use, higher density helps to reduce the porosity of the furnace lining material and reduce stress concentration areas, thereby effectively improving the material's crack resistance. This is especially important in the high-temperature and high-pressure environment of the medium-frequency furnace, which can significantly reduce the risk of cracking of the furnace lining during use and extend its service life.

[0099] In some embodiments, a planetary mixing device is used for mixing. During the mixing process, the speed of the device is controlled to be 50 to 120 rpm. The added water is evenly introduced by spraying and is gradually added during the mixing process. The addition time is controlled within 3 to 5 minutes. The mixing time is 5 to 10 minutes until a mixture with good uniformity is formed.

[0100] In the above embodiment, a planetary mixing device is used to mix the raw materials. This device can effectively mix quartz sand and boric acid particles of different particle sizes by a multi-directional rotating stirring method. Compared with traditional stirring equipment, the planetary mixing device can achieve uniform mixing in a short time, especially for raw materials with a wide range of particle sizes and large density differences. The effect is more significant. This efficient mixing method can avoid unstable material properties due to uneven mixing, and lay a stable foundation for subsequent processes.

[0101] In addition, this embodiment limits the equipment speed, the method and time of adding water during the mixing process, and limits the speed of the planetary mixing equipment to 50-120 rpm, which can effectively avoid the problem that too high a speed may cause the quartz sand particles to break or the fine-grained sand to agglomerate. In addition, by gradually adding water by spraying, it can ensure that the water is evenly distributed, while avoiding adding a large amount of water at one time to cause excessive local humidity. This precise parameter control can not only improve the mixing effect, but also well protect the original structure of the material particles, so that the physical properties of the raw materials are not affected.

[0102] The mixing time is 5 to 10 minutes, which can ensure the uniformity of the mixture and avoid increased energy consumption or reduced process efficiency due to long mixing. In addition, the introduction of water by spraying and clear time control (gradual addition within 3 to 5 minutes) make the mixing operation more repeatable and consistent. This method simplifies the complexity of industrial operations and optimizes production efficiency. At the same time, it provides more uniform raw materials for subsequent molding and sintering processes, thereby ensuring the consistency of material properties.

[0103] In some embodiments, during the baking stage, the furnace lining material is subjected to a sintering process of gradually increasing the temperature in stages as follows:

[0104] Initial heating stage: gradually raise the temperature from room temperature to 200°C to remove moisture and volatile impurities in the mixture;

[0105] Intermediate heating stage: gradually increase the temperature from 200°C to 1250°C and keep it at 600-800°C for 2-4 hours to achieve the initial transformation of the low-temperature crystal form of quartz sand to the high-temperature crystal form and reduce the pores between the particles;

[0106] Final heating stage: gradually increase the temperature from 1250°C to 1350-1400°C and keep it warm for 4-6 hours to achieve a full transformation of the quartz sand crystal form and form a dense high-temperature bonding structure between the particles;

[0107] The heating rate of the entire sintering process is controlled at 0.5-1°C / minute, and the duration is not less than 36 hours. After the final heating stage is completed, the furnace lining material should be slowly cooled to avoid cracks or deformation caused by thermal stress caused by sudden cooling. The cooling rate can be controlled at 2-5°C / minute, gradually decreasing from 1350-1400°C to room temperature (about 20°C). During the cooling process, the furnace lining material is kept in a closed or semi-closed state to avoid thermal stress concentration caused by rapid cooling. This cooling process ensures the crystal stability and density of the furnace lining material, providing reliable guarantee for its stable use in subsequent high-temperature smelting environments.

[0108] In this embodiment, the sintering process is divided into three stages: initial heating, intermediate heating, and final heating. This staged heating design can effectively avoid thermal stress concentration caused by rapid heating, especially inside the material. In the initial heating stage, the temperature is gradually raised from room temperature to 200°C, and the water and volatile impurities in the mixture are removed by slowly heating to prevent the surface of the material from cracking or loosening of the structure due to rapid evaporation of water. This process provides a good foundation for the stable heating in the subsequent high-temperature stage.

[0109] In the design of the intermediate heating stage, this embodiment is kept warm for 2 to 4 hours in the key temperature zone of 600 to 800 ° C. This stage is the key moment when the quartz sand crystal form changes from the low temperature type to the high temperature type. By appropriately extending the insulation time, the initial transformation of the crystal form can be fully completed. This not only reduces the volume change in the subsequent high temperature stage, but also optimizes the arrangement of particles and reduces the porosity of the material. The rearrangement and combination of particles are initially completed at this stage, which lays the foundation for the high temperature densification of the material and helps to improve the compressive performance and high temperature stability of the furnace lining.

[0110] In the final heating stage, the temperature is gradually raised to 1350-1400°C and kept warm for 4-6 hours. This method can fully transform the crystal form of the material at high temperature and achieve high-temperature bonding between particles. The 4-6 hours of insulation time provides sufficient time for the surface reaction and diffusion of the particles, making the material structure more compact. In addition, the heating rate is controlled at 0.5-1°C / minute, and the entire sintering time is not less than 36 hours, which can further reduce the impact of temperature differences on the material and avoid local cracking or performance degradation caused by uneven temperature during the sintering process. In this way, a furnace lining material with stable performance and high density is finally formed.

[0111] In some embodiments, the forming step comprises:

[0112] The mixture is laid layer by layer on the furnace wall by combining mechanical vibration equipment and manual tamping tools; the thickness of each layer is 3 to 5 mm;

[0113] Use mechanical vibration equipment to vibrate and compact each layer of the mixture at a frequency of 300 to 500 times per minute and a vibration time of 30 to 60 seconds;

[0114] After each layer is laid, manual tamping tools are used to perform additional compaction on the corners and complex areas to ensure overall density and uniformity.

[0115] In the above embodiment, a design method is adopted in which the mixed material is laid thinly layer by layer in the furnace wall, and the thickness of each layer is 3 to 5 mm. This thin layer laying method can effectively avoid the problem of insufficient material density caused by laying too thick a single time, especially at the edge of the furnace wall and parts with complex shapes. Thin layer laying can more easily ensure the uniformity of the material. At the same time, laying layer by layer provides sufficient compaction time for each layer, so that the adhesion between the material and the furnace wall can be significantly improved. This embodiment can achieve close stacking of materials and good adhesion, thereby effectively improving the overall structural strength of the furnace lining and avoiding peeling or cracking in subsequent use.

[0116] In addition, the scheme of this embodiment uses mechanical vibration equipment to vibrate and compact each layer of the mixture, with a vibration frequency of 300 to 500 times / minute and a vibration time of 30 to 60 seconds. This process can rearrange the particles under the action of vibration force through high-frequency vibration, which helps to reduce the void ratio between particles. High-frequency vibration is particularly suitable for filling the tiny pores of fine-grained quartz sand, further improving the density of the material. In addition, reasonable control of the vibration time of 30 to 60 seconds and the vibration frequency of 300 to 500 times / minute can not only ensure the compaction effect, but also avoid the damage to the particle structure by excessive vibration, providing a more stable basic material for subsequent high-temperature sintering.

[0117] In addition to mechanical vibration, this embodiment also uses manual tamping tools to perform additional compaction on corners and complex areas. Corners and complex areas are difficult to completely cover with mechanical equipment, and are prone to become weak points with insufficient density. Manual tamping can solve this problem in a targeted manner by tapping point by point, ensuring the density and uniformity of the material in these areas. This embodiment combines manual operation with mechanical vibration to make up for the limitations of mechanical equipment and further improve the overall performance of the furnace lining, especially in high-temperature environments. It has stronger crack resistance and provides a solid guarantee for the realization of high-quality high-temperature resistant furnace lining materials.

[0118] In some embodiments, the mechanical vibration device used is a handheld high-frequency vibrator, and the manual tamping tool used is a metal impact hammer. The hammer head of the metal impact hammer is a conical metal structure, and the weight of the hammer head is 0.5 to 1.5 kilograms.

[0119] The use of handheld high-frequency vibrators as mechanical vibration equipment can make the use of vibration equipment more flexible. Operators can flexibly adjust the position and angle of the vibrator as needed, especially at the edge or complex parts of the furnace wall. Handheld high-frequency vibrators can easily reach areas that are difficult to cover with fixed mechanical equipment. In addition, high-frequency vibration can promote the rearrangement and accumulation of quartz sand particles, fill the gaps between particles, significantly improve the density and uniformity of the material, and provide a more stable foundation for the subsequent high-temperature sintering of the furnace lining material.

[0120] At the same time, in this embodiment, the manual tamping tool is a metal impact hammer, and the hammer head is designed as a conical metal structure with a weight controlled at 0.5 to 1.5 kg. This hammer head design can concentrate the impact force and is particularly suitable for processing the corners of furnace walls or other complex-shaped areas. During use, the mixture can be further compacted by manually tapping point by point to improve the density of these areas and avoid the risk of cracking or peeling caused by insufficient local density. Moreover, the conical hammer head also facilitates precise operation of subtle areas.

[0121] In practical applications, a handheld high-frequency vibrator is used to compact evenly over a large area, while a metal impact hammer is used to deal with complex parts in a targeted manner. The combination of the two can significantly improve construction efficiency. Compared with the use of mechanical vibration equipment or manual tamping alone, the combination of mechanical and manual methods can not only ensure construction efficiency, but also take into account quality details. Through this comprehensive process, the overall molding quality of the furnace lining material can be improved, especially during high-temperature use, its crack resistance and durability are significantly enhanced.

[0122] In some embodiments, during the sintering process, an infrared temperature control device is used to monitor the temperature in real time during the insulation stage of 600-800°C, and the temperature difference is controlled within ±2°C.

[0123] During the sintering process, in the insulation stage of 600-800℃, the temperature is monitored in real time by using infrared temperature control equipment, and the temperature difference is controlled within ±2℃. This can accurately grasp the temperature changes in the key temperature zones during the sintering process and avoid local temperature deviations caused by hysteresis or uneven heating in traditional temperature control methods. In the temperature range of 600-800℃, the crystal transformation and particle rearrangement of quartz sand are key process links. Real-time monitoring and precise temperature control can ensure the stability of this transformation process and avoid incomplete crystal transformation or poor particle bonding due to excessive temperature differences.

[0124] In addition, real-time monitoring and adjustment of temperature by infrared temperature control equipment can significantly improve the temperature uniformity of furnace lining materials during the insulation stage. Especially in the critical temperature zone of 600-800℃, if the temperature difference is large, stress concentration is likely to occur inside the material due to uneven thermal expansion. These internal stresses may evolve into cracks during subsequent heating or use stages, reducing the service life of the material. By controlling the temperature difference within ±2℃, the internal stress of the material can be effectively reduced, and the crack resistance and high-temperature stability of the furnace lining material can be improved. In addition, precise temperature monitoring and control not only helps to fully combine particles, but also significantly optimizes the density of the material. By precisely controlling the temperature, it is helpful to ensure uniform sintering of particles in each area and reduce the formation of pores, thereby improving the overall density and compressive strength of the material, thus laying a solid foundation for reliable use in high-temperature environments.

[0125] In some embodiments, the temperature of the water added during the mixing process is 20°C to 40°C.

[0126] In this embodiment, it is proposed that the temperature range of the water added during the mixing process is 20°C to 40°C, which combines the actual industrial operation requirements and material characteristics. Warm water has good fluidity and wetting properties, and can quickly and evenly cover the surface of quartz sand particles, especially fine-grained sand. Compared with cold water, water in this temperature range can significantly improve the bonding efficiency between particles during the mixing process, avoid local drying or insufficient humidity, and thus ensure the overall uniformity of the mixture.

[0127] During the mixing process, if the water temperature is too low, a highly viscous water film will form on the surface of the quartz sand, increasing the risk of agglomeration of fine-grained sand. When the temperature is higher than 40°C, the evaporation of water will accelerate, which will result in insufficient time to wet the particles and reduce the mixing effect. Controlling the water temperature between 20°C and 40°C can wet the surface of the particles while avoiding excessive evaporation and reducing the possibility of particle agglomeration. In addition, this temperature range has no negative impact on the physical structure of the quartz sand particles, and can well protect the original properties of the particles and ensure the final quality of the furnace lining material.

[0128] In some embodiments, the silicon dioxide content of the high-purity quartz sand used is not less than 99.9%. Using such high-purity raw materials can significantly reduce the interference of impurities in the sintering process.

[0129] The following is further described in conjunction with specific embodiments:

[0130] Example 1

[0131] In this embodiment, a high-temperature resistant lining material for a medium-frequency furnace is prepared by weighing high-purity quartz sand according to the following weight percentages:

[0132] Particle size 2-4 mesh: 5%;

[0133] Particle size 4-6 mesh: 6%;

[0134] Particle size 6-8 mesh: 6%;

[0135] Particle size 8-10 mesh: 12%;

[0136] Particle size 10-20 mesh: 17.5%;

[0137] Particle size 20-40 mesh: 17.5%;

[0138] Particle size 40-70 mesh: 12.5%;

[0139] Particle size is 120-150 mesh: 23.5%.

[0140] The sum of the weight percentages of the above 8 groups of high-purity quartz sand particle sizes is 100%, and the amount of boric acid added is 1.2% of the total weight of the quartz sand.

[0141] Process flow:

[0142] Mixing: Use planetary mixer at 100 rpm for 10 minutes. Water is gradually introduced by spraying at a ratio of 0.8% of the total weight of the mixture.

[0143] Forming: Lay thin layers one by one, with each layer 4 mm thick, use a handheld high-frequency vibrator to vibrate and compact (400 times / minute, 30 seconds), and manually tamp the edges and corners.

[0144] bake:

[0145] Initial heating stage: from room temperature to 200°C, lasting for 3 hours;

[0146] Intermediate heating stage: from 200°C to 1250°C, heating rate 0.5°C / min, keeping at 700°C for 3 hours during heating;

[0147] Final heating stage: from 1250°C to 1400°C, the heating rate is controlled at 0.5-1°C / min, and then kept at 1400°C for 5 hours.

[0148] The total sintering time is not less than 36 hours.

[0149] The furnace lining material samples prepared in this embodiment have the following performance parameters after testing:

[0150] Performance Indicators Measurement results Porosity 6% Compressive strength 85MPa High temperature resistance >1500℃ Thermal expansion coefficient (20~1000℃) <![CDATA[5.8×10 -6 / ℃]]> Service life (industrial application) >12 months

[0151] As can be seen from the table above, the porosity of the furnace lining material sample prepared in this embodiment is only 6%, the structural density is excellent, and the compressive strength reaches 85MPa, which can meet the use requirements of the medium frequency furnace under high pressure and high temperature conditions. Moreover, the high temperature resistance of the furnace lining material is significantly improved, and it can be used stably for a long time. In the actual industrial test, the service life is extended to more than 12 months, and the total smelting furnace times exceeds 800 times.

[0152] In this embodiment, the following test method is used to test the long-term service life of the furnace lining material prepared in this embodiment. The test method is as follows:

[0153] In the actual industrial medium frequency furnace environment, the prepared furnace lining material is tested for long-term service life. Each smelting process involves the following stages:

[0154] High temperature smelting: the working temperature is 1600℃, and each smelting time is about 3 hours;

[0155] Cooling stage: After the smelting is completed, the temperature of the furnace lining gradually cools down to room temperature (about 20°C) and prepares for the next smelting.

[0156] Complete 2 to 3 complete high temperature cycle tests every day, the continuous test period is 12 months, and the total melting furnace times exceed 800 times. In the continuous operation of more than 800 times, the furnace lining material showed excellent thermal shock resistance, no obvious cracks or peeling, significantly reducing the frequency of shutdown maintenance, and the extension of service life not only reduced the cost of material replacement, but also improved the production efficiency of the medium frequency furnace.

[0157] Example 2

[0158] In this embodiment, high-purity quartz sand is weighed according to the following weight percentages:

[0159] Particle size 2-4 mesh: 5%;

[0160] Particle size 4-6 mesh: 6%;

[0161] Particle size 6-8 mesh: 6%;

[0162] Particle size 8-10 mesh: 12%;

[0163] Particle size 10-20 mesh: 18%;

[0164] Particle size 20-40 mesh: 18%;

[0165] Particle size 40-70 mesh: 12%;

[0166] Particle size is 120-150 mesh: 23%.

[0167] The sum of the weight percentages of the above 8 groups of high-purity quartz sand particle sizes is 100%, and the amount of boric acid added is 1.0% of the total weight of the quartz sand.

[0168] Process flow:

[0169] Mixing: Use planetary mixer, speed 80 rpm, mixing time 8 minutes, water ratio 0.6% of the total weight of the mixture, water temperature 25°C.

[0170] Forming: Lay layer by layer, each layer is 5 mm thick, use a handheld high-frequency vibrator to vibrate and compact (350 times / minute, 40 seconds), and manually tamp the edges and corners.

[0171] Baking: Same as Example 1, except that in the final heating stage, the temperature was finally raised to 1380°C and kept at that temperature for 4 hours.

[0172] Example 3

[0173] In this embodiment, high-purity quartz sand is weighed according to the following weight percentages:

[0174] Particle size 2-4 mesh: 6%;

[0175] Particle size 4-6 mesh: 7%;

[0176] Particle size 6-8 mesh: 7%;

[0177] Particle size 8-10 mesh: 14%;

[0178] Particle size 10-20 mesh: 16%;

[0179] Particle size 20-40 mesh: 16%;

[0180] Particle size 40-70 mesh: 12%;

[0181] Particle size is 120-150 mesh: 22%.

[0182] The sum of the weight percentages of the above 8 groups of high-purity quartz sand particle sizes is 100%, and the amount of boric acid added is 1.3% of the total weight of the quartz sand.

[0183] The process flow is basically the same as that of the embodiment, except that in the intermediate heating stage, the heating rate is controlled at 0.8°C / min, and the temperature is kept at 650°C for 4 hours; in the final heating stage, the temperature is finally raised to 1370°C and kept for 4 hours.

[0184] Example 4

[0185] In this embodiment, high-purity quartz sand is weighed according to the following weight percentages:

[0186] Particle size 2-4 mesh: 4%;

[0187] Particle size 4-6 mesh: 6%;

[0188] Particle size 6-8 mesh: 6%;

[0189] Particle size 8-10 mesh: 10%;

[0190] Particle size 10-20 mesh: 18%;

[0191] Particle size 20-40 mesh: 18%;

[0192] Particle size 40-70 mesh: 14%;

[0193] Particle size is 120-150 mesh: 24%.

[0194] The sum of the weight percentages of the above 8 groups of high-purity quartz sand particle sizes is 100%, and the amount of boric acid added is 1.1% of the total weight of the quartz sand.

[0195] The process flow is basically the same as that of the embodiment, except that in the intermediate heating stage, the heating rate is controlled at 0.6°C / min, and the temperature is kept at 680°C for 4 hours.

[0196] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a high temperature resistant lining material for a medium frequency furnace, characterized in that: The following steps are involved: Raw material ratio: high-purity quartz sand and boric acid are weighed according to weight ratio; wherein the quartz sand includes a plurality of particle size ranges covering at least five particle sizes, and the quartz sand of each particle size in the quartz sand composition adopts a non-uniform gradient distribution mode, the ratio of the maximum particle size to the minimum particle size of the quartz sand is greater than 60, the minimum particle size is fine-grained quartz sand with a particle size range of 120 to 150 meshes, and the fine-grained quartz sand with a particle size range of 120 to 150 meshes accounts for 20% to 30% of the total weight of the quartz sand; the amount of boric acid used is 0.8% to 1.5% of the total weight of the quartz sand; Mixing: The quartz sand and boric acid are fully mixed by a mixing device to form a uniform mixture; a small amount of water is added to the mixture during the mixing process, and the weight proportion of the water does not exceed 0.8% of the total weight of the mixture; Forming: The mixture is laid on the furnace wall in a thin layer-by-layer tamping manner, with each layer thickness not exceeding 5 mm; mechanical vibration equipment is used to assist in the tamping process to improve density and adhesion; Baking: The furnace lining material is heated up gradually in stages, and the sintering temperature is 1250-1400℃. High-temperature baking and sintering are completed in stages to achieve the crystal transformation of quartz sand and structural densification of the material.

2. The method for preparing a high temperature resistant lining material for a medium frequency furnace according to claim 1, characterized in that: The particle size range of the quartz sand used includes the following particle sizes: 2-4 mesh, 4-6 mesh, 6-8 mesh, 8-10 mesh, 10-20 mesh, 20-40 mesh, 40-70 mesh and 120-150 mesh; When mixing the raw materials, weigh the raw materials according to the following weight percentages: High-purity quartz sand with a particle size of 2 to 4 mesh: 4% to 6%; High-purity quartz sand with a particle size of 4-6 mesh: 5%-7%; High-purity quartz sand with a particle size of 6-8 mesh: 5%-7%; High-purity quartz sand with a particle size of 8-10 mesh: 10%-14%; High-purity quartz sand with a particle size of 10-20 mesh: 16%-18%; High-purity quartz sand with a particle size of 20-40 mesh: 16%-18%; High-purity quartz sand with a particle size of 40-70 mesh: 12%-14%; High-purity quartz sand with a particle size of 120-150 mesh: 22%-24%; The dosage of boric acid is 1.0% to 1.3% of the total weight of quartz sand.

3. The method for preparing a high temperature resistant lining material for a medium frequency furnace according to claim 2, characterized in that: When mixing the raw materials, weigh the raw materials according to the following weight percentages: High-purity quartz sand with a particle size of 2 to 4 mesh: 5%; High-purity quartz sand with a particle size of 4-6 mesh: 6%; High-purity quartz sand with a particle size of 6-8 mesh: 6%; High-purity quartz sand with a particle size of 8-10 mesh: 12%; High-purity quartz sand with a particle size of 10-20 mesh: 17.5%; High-purity quartz sand with a particle size of 20-40 mesh: 17.5%; High-purity quartz sand with a particle size of 40-70 mesh: 12.5%; High-purity quartz sand with a particle size of 120-150 mesh: 23.5%; The amount of boric acid used is 1.2% of the total weight of quartz sand.

4. The method for preparing a high temperature resistant lining material for a medium frequency furnace according to any one of claims 1 to 3, characterized in that: A planetary mixing device is used for mixing. During the mixing process, the speed of the device is controlled to be 50 to 120 rpm. The added water is evenly introduced by spraying and is gradually added during the mixing process. The adding time is controlled within 3 to 5 minutes and the mixing time is 5 to 10 minutes until a mixture with good uniformity is formed.

5. The method for preparing a high temperature resistant lining material for a medium frequency furnace according to claim 1, characterized in that: During the baking stage, the sintering process of the furnace lining material is carried out in stages with gradually increasing temperature as follows: Initial heating stage: gradually raise the temperature from room temperature to 200°C to remove moisture and volatile impurities in the mixture; Intermediate heating stage: gradually increase the temperature from 200°C to 1250°C and keep it at 600-800°C for 2-4 hours to achieve the initial transformation of the low-temperature crystal form of quartz sand to the high-temperature crystal form and reduce the pores between the particles; Final heating stage: gradually increase the temperature from 1250℃ to 1350~1400℃ and keep it for 4~6 hours to achieve full transformation of the quartz sand crystal form and form a dense high-temperature bonding structure between the particles; The heating rate of the entire sintering process is controlled at 0.5-1°C / minute and lasts for no less than 36 hours.

6. The method for preparing a high temperature resistant lining material for a medium frequency furnace according to claim 1, characterized in that: The forming step comprises: The mixture is laid layer by layer on the furnace wall by combining mechanical vibration equipment and manual tamping tools; the thickness of each layer is 3 to 5 mm; Use mechanical vibration equipment to vibrate and compact each layer of the mixture at a frequency of 300 to 500 times per minute and a vibration time of 30 to 60 seconds; After each layer is laid, manual tamping tools are used to perform additional compaction on the corners and complex areas to ensure overall density and uniformity.

7. The method for preparing a high temperature resistant lining material for a medium frequency furnace according to claim 6, characterized in that: The mechanical vibration equipment used is a handheld high-frequency vibrator, and the manual tamping tool used is a metal impact hammer. The hammer head of the metal impact hammer is a conical metal structure, and the weight of the hammer head is 0.5 to 1.5 kilograms.

8. The method for preparing a high temperature resistant lining material for a medium frequency furnace according to claim 5, characterized in that: During the sintering process, infrared temperature control equipment is used to monitor the temperature in real time during the insulation stage of 600-800°C, and the temperature difference is controlled within ±2°C.

9. The method for preparing a high temperature resistant lining material for a medium frequency furnace according to claim 4, characterized in that: The temperature of the water added during the mixing process is 20°C to 40°C.

10. The method for preparing a high temperature resistant lining material for a medium frequency furnace according to any one of claims 1 to 9, characterized in that: The silicon dioxide content of the high-purity quartz sand used is not less than 99.9%.